Demensia : Patofisiologi, Faktor Resiko dan Peran Inflamasi dalam Perkembangan Penyakit - Erick Sidarta; Triyana Sari; Sari Mariyati Dewi Nataprawira (Pusat Riset dan Inovasi Nasional, 2025)
Dementia is a complex neurodegenerative syndrome characterized by cognitive decline, including memory impairment, difficulty in thinking, and social interaction, which can affect daily activities. This condition is often caused by other diseases, including Alzheimer’s disease, vascular dementia, Lewy body dementia, and frontotemporal dementia, each with unique pathological mechanisms. Alzheimer’s disease, the leading cause of dementia, involves the accumulation of beta-amyloid plaques and tau tangles that disrupt neuronal function and trigger chronic inflammation. Vascular dementia results from impaired blood flow to the brain, while Lewy body dementia is associated with the misfolding of alpha-synuclein protein. Meanwhile, frontotemporal dementia is linked to the accumulation of tau or TDP-43 proteins, causing degeneration of the frontal and temporal lobes. Aging is the primary risk factor for dementia through the process of inflammaging, a low-grade chronic inflammation caused by persistent activation of the immune system. Inflammaging accelerates neurodegeneration by increasing oxidative stress, mitochondrial dysfunction, and the accumulation of pathological proteins. Additionally, neuroinflammation plays a crucial role by over activating microglia, which exacerbates neuronal damage. The combination of inflammation as both a trigger and a consequence create a pathological cycle that accelerates the progression of dementia. Preventive strategies include managing modifiable risk factors such as hypertension, diabetes, obesity, and adopting a healthy lifestyle, alongside developing therapies targeting inflammaging and neuroinflammation. A deeper understanding of these pathophysiological and inflammatory mechanisms is essential to support the development of multidisciplinary interventions to reduce the global burden of dementia.